Mindfulness-Based Interventions for Metabolic Syndrome in The Elderly: A Review of Evidence on Psychological and Physiological Outcomes - Pradhiba SPM; Thephilah Cathrine R; Jayanthi P (Medsci Publications, 2024)
Background: Metabolic syndrome poses a significant health challenge in the elderly, affecting both psychological and physiological aspects. The application of mindfulness in treating the lifestyle variables linked to the risk of cardiovascular disease shows promise in improving self-awareness, mood regulation, and attention control. In addition to lowering stress, anxiety, and depression in elderly, mindfulness therapies have the potential to improve glycemic management. This study aims to investigate the potential efficacy of mindfulness-based interventions in addressing this complex issue. Methods: The Cochrane Library, Embase, and PubMed/MEDLINE electronic databases were searched by the author to find pertinent systematic reviews and meta-analyses. Results: A summary of the available research review explores the impact of mindfulness-based interventions on elderly individuals with metabolic syndrome from years 2011-2023. Examining both psychological and physiological outcomes, the study focuses on depression, quality of life, and key health indicators such as BMI, cholesterol levels, and blood sugar. Conclusion: Findings shed light on the potential benefits of mindfulness practices in improving mental well-being and positively influencing metabolic parameters in the elderly population. To fully understand the biological impacts of mindfulness on human physiological processes, more investigation is required.